Improving the models for prognosis of aneurysmal subarachnoid hemorrhage with the neutrophil-to-albumin ratio - Zhang, Renjie; Liu, Zheran; Zhang, Yu; Pei, Yiyan; He, Yan; Yu, Jiayi; You, Chao; Ma, Lu; Fang, Fang (Frontiers in Neurology, 2023)
Objective Many peripheral inflammatory markers were reported to be associated with the prognosis of aneurysmal subarachnoid hemorrhage (aSAH). We aimed to identify the most promising inflammatory factor that can improve existing predictive models. Methods The study was based on data from a 10 year retrospective cohort study at Sichuan University West China Hospital. We selected the well-known SAFIRE and Subarachnoid Hemorrhage International Trialists’ (SAHIT) models as the basic models. We compared the performance of the models after including the inflammatory markers and that of the original models. The developed models were internally and temporally validated. Results A total of 3,173 patients were included in this study, divided into the derivation cohort (n = 2,525) and the validation cohort (n = 648). Most inflammatory markers could improve the SAH model for mortality prediction in patients with aSAH, and the neutrophil-to-albumin ratio (NAR) performed best among all the included inflammatory markers. By incorporating NAR, the modified SAFIRE and SAHIT models improved the area under the receiver operator characteristics curve (SAFIRE+NAR vs. SAFIRE: 0.794 vs. 0.778, p = 0.012; SAHIT+NAR vs. SAHIT: 0.831 vs. 0.819, p = 0.016) and categorical net reclassification improvement (SAFIRE+NAR: 0.0727, p = 0.002; SAHIT+NAR: 0.0810, p < 0.001). Conclusion This study illustrated that among the inflammatory markers associated with aSAH prognosis, NAR could improve the SAFIRE and SAHIT models for 3 month mortality of aSAH.